"Gatekeeper or crisis manager? Coverage of "Lahad Datu" conflict" - Ambikapathy, Manimegalai; Zanuddin, Hasmah (Science Publishing Corporation, 2018)
Lahad Datu conflict also known as "Sabah standoff" conflict, is unforgettable tragedies until killed about 10 of Malaysian security personnel and impacted economic, social and emotion of citizens especially at Lahad Datu, Sabah. The objective of this research is to examine the portrayal of solution from Malaysian Government for the "Lahad Datu Crisis" through newspaper framing in Malaysian mainstream newspapers namely Utusan Malaysia, The Star, Sin Chew and Nanban daily. The measurement for the crisis response will be measure through few independent variables such as category of "Lahad Datu" news; between problem, solution, people or neutral category. The following independent variable is through the slants of news; whether news is slanted in positive, negative or neutral slant. With the assistance of "Situational Crisis Communication Theory", this research employed a systematic quantitative content analysis to gather the data. Finding revealed that, category of solution appeared most in Utusan Malaysia, The Star, Sin Chew and Nanban daily and news in positive slants were covered in all the selected dailies. In providing responses for the crisis, Justification and Concern crisis response portrayed most, however, through Kruskal Wallis test, data found that The Star and Utusan Malaysia portrayed most of the Justification and Concern responses compare to Sin Chew daily and Nanban daily.